Mitogenome of Xya pfaendleri (Orthoptera: Caelifera): Its comparative description and phylogenetic position within Tridactylidea - Yahyaoğlu, Özgül; Doğan, Ceren Tutku; Uluar, Onur; Karakaş, Müşerref Y.; Çiplak, Battal (Zootaxa, 2023)
We report the comparative examination of the complete mitochondrial genome of the pygmy mole cricket Xya pfaendleri (Orthoptera: Caelifera: Tridactylidae). The mitogenome consists of 13 protein-coding regions, 22 tRNAs, two rRNAs, and one control region, following the gene order of the ancestral pancrustacean mitogenome. The length of the mitogenome in Xya pfaendleri is 15352 bp. The start and stop codons of the protein-coding genes exhibit the general pattern observed in orthopterans. The data indicate that the pattern of gene overlapping/intergenic sequences exhibits a significant phylogenetic signal. A phylogenetic tree inferred using 12 mitogenomes (seven belonging to Tridactylidea, three to Acrididea, and two to Ensifera) confirms the sister group relationship of Acrididea and Tridactylidea. The relationship among the families of Tridactylidea is Cylindrachetidae + (Ripipterygidae + Tridactylidae). The mitogenome sequences of Xya and Tridactylus constitute a single clade, sharing a last common ancestor 94 million years ago, and rendering the first genus paraphyletic. The present preliminary data suggest that we still have much to learn about the evolution and diversity of Tridactylidea.